PERBANDINGAN NILAI HEMOGLOBIN PADA PASIEN GAGAL GINJAL KRONIK DENGAN RIWAYAT DIABETES MELITUS DAN HIPERTENSI - Cintami Nida Fajriani (2022)
Chronic Kidney Failure (CKD), is damage to the kidneys caused by a decrease in the glomerular filtration rate (GFR) < 60 mL/min /1.73 m2 that occurs for 3 months or more. Most CKD is caused by diabetes mellitus (DM) and hypertension. CKD causes decreased erythropoietin resulting decrease hemoglobin (Hb). Objective: To determine the relationship between the characteristics of CKD patients, history of DM, hypertension, and Hb value. Comparing Hb values in CKD patients with DM and hypertension. Methods: Used a cross-sectional design with a causal comparison. Have 89 CKD respondents from October-December 2021 at the RSUD Kabupaten Bekasi. Collecting data using observation sheets of patient medical records. Results: CKD respondents who have a history of DM (22.5%) and who have a history of hypertension (77.5%). The Mann-Whitney U test results obtained p-value = 0.091 (p-value > 0.05) for the relationship Dm and Hb, p-value = 0.091 (p-value > 0.05) for relationship hypertension and Hb, p-value = 0.091 (p-value > 0.05) for differences Hb values of CKD with DM and hypertension. This study concludes that there is no significant difference in Hb levels in CKD patients with DM and Hb values in CKD patients with hypertension.